2012
DOI: 10.2165/11598490-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

In Support of Early Surgery for Hip Fractures Sustained by Elderly Patients Taking Clopidogrel

Abstract: Early surgical intervention for hip fracture in patients receiving long-term treatment with clopidogrel appears to be safe in terms of bleeding complications. It has the potential to enable earlier mobilization and shorter hospitalization and may reduce mortality and complications associated with immobilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 12 publications
3
30
0
Order By: Relevance
“…Thirty-one studies deemed to be relevant to the research question underwent full text review. Studies were excluded for the following reasons: Japanese language (1) [35]; paper was unavailable for review (1) [33]; clopidogrel group had a mean time to surgery of >7 days and was therefore felt to be non-comparable (2) [38,39]; letters (3) [36,40,41]; no comparison group (2) [42,43]; no relevant data (1) [34]; abstract only (1) [44]; surveys (3) [22,23,24]; no clopidogrel group (1) [45]; included patients on other antiplatelets (1) [32,46] and early surgery >48 h (2) [47,48] This left 12 studies, which were included in the review [30,31,[49][50][51][52][53][54][55][56][57][58].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-one studies deemed to be relevant to the research question underwent full text review. Studies were excluded for the following reasons: Japanese language (1) [35]; paper was unavailable for review (1) [33]; clopidogrel group had a mean time to surgery of >7 days and was therefore felt to be non-comparable (2) [38,39]; letters (3) [36,40,41]; no comparison group (2) [42,43]; no relevant data (1) [34]; abstract only (1) [44]; surveys (3) [22,23,24]; no clopidogrel group (1) [45]; included patients on other antiplatelets (1) [32,46] and early surgery >48 h (2) [47,48] This left 12 studies, which were included in the review [30,31,[49][50][51][52][53][54][55][56][57][58].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…On meta-regression, neither mean age (p = 0.268) nor percentage female (p = 0.963) could predict differences in mortality. Three studies [31,55,58] reported mortality outcomes in early versus delayed surgery. Overall, the odds ratio for mortality was 0.61 (95% CI: 0.11-3.25).…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In another paper, Chechik et al compared 30 patients who were on clopidogrel and underwent early surgery (mean time: 1 day and 16 hours, SD: 1 day) with a group of patients who underwent delayed surgery (mean time: 7 days and 12 hours, SD: 2 days and 17 hours). 19 They found that the early treatment group had a shorter hospital stay than the delayed group (11 vs 17 days, p=0.0002). Even though the mortality rates were similar, there were more complications related to prolonged immobilisation in the delayed treatment group.…”
Section: Discussionmentioning
confidence: 95%
“…3,4 There is a paucity of literature reporting the risks and benefits of operating on these patients. 5,6 This study sought to determine whether time to surgery influenced factors including drop in haemoglobin (Hb) levels, need for blood transfusion, duration of inpatient stay and 30-day mortality for patients who were admitted with a neck of femur fracture while taking clopidogrel. …”
mentioning
confidence: 99%